Knowledge, practice and attitudes of healthcare students to sepsis management in Jamaica - Karen J. Roye-Green; Ivan Vickers; Sharon Priestley; Jerome Walker; Rohan Willis (BMC Medical Education)
Abstract Background Sepsis is a medical emergency requiring timely management and available global evidence suggests that healthcare workers and students are poorly prepared to effectively diagnose and treat such patients. This study evaluates the inter-relationship of healthcare students’ attitudes towards, knowledge of and practice of sepsis management as they progress through training in Jamaica. Methods A prospective cross-sectional survey using an anonymous self-administered questionnaire with convenience sampling was performed among healthcare students at all levels of training. All available medical and nursing students from the major public medical and nursing schools in the Kingston Metropolitan Area were included in the study. The questionnaire was composed of 25 items covering aspects of the knowledge, attitudes, and practice of sepsis management. Results The study population consisted of 292 respondents; 210 medical and 82 nursing students. The need for fluid resuscitation before ICU admission (72.6%) was the practice question that was correctly identified by the majority of students. Most of the remaining items were correctly identified by approximately half of the students including signs of sepsis such as altered mental state (56.1%), low systolic blood pressure (53.7%) and tachypnea (50.6%). In contrast, very few students could identify the signs that indicated the presence of septic shock such as high serum lactate and the need for vasopressors and only 7% of students knew the correct annual sepsis mortality rate. Nursing students had higher overall mean correct knowledge and correct practice scores compared to medical students and lower incorrect practice scores, although there was no difference in incorrect knowledge scores between the 2 respondent groups. A subgroup analysis of students in their final stage of training revealed a more comparable performance of the 2 student groups, highlighting the improved performance by both nursing and medical students who received either formal sepsis training or were in the late stage of training. Jamaican healthcare students agree that more training on sepsis is needed (98.3%) and that sepsis care bundles should be implemented during their training courses (94.2%). Conclusions This study revealed differences in the healthcare students’ attitudes, knowledge of and practice of sepsis in Jamaica. There is the need for training on sepsis and implementation of sepsis care bundles.